Computer-aided analysis using MATLAB radar range equation as an alternative method for evaluating air defense surveillance radar - Lat, Pabbie Matanguihan (Animo Repository, 2006)
This paper presents a numerical computer-aided analysis and design of program using MATLAB software as the authors alternative evaluation method proposal for the Philippine Air Force (PAF) Air Defense Surveillance Radar (ADSR); a vital requirement for its acquisition under the Armed Forces of the Philippines (AFP) Modernization Program. The study establishes a mathematical procedure that will complement the AFPs analytical model called Cost Operational Effectiveness Analysis (COEA), which was found to be inadequate for evaluating complex equipment such as the radars. First, the study succeeded in establishing the appropriate radar equation for the solution of a near-approximation analysis of radar performance inspired by the widely accepted Lamont V. Blakes Pulse-Radar-Range manual calculation method. Second, the study demonstrated the feasibility of translating the radar range equation into a MATLAB program designed as a computer-aided solution for calculating iterated range prediction outputs and a corresponding graphical solution for both lossless and non-lossless conditions. Third, the radar parameters used in the designed MATLAB radar-range equation program were identified and defined as the new baseline standard test criteria addendum to the PAF Circular of Requirement (COR) document, namely: Radar Range Factors; Radar System Noise Temperature Factors; Detectability Factors; Loss Factors; and, Pattern Propagation Factors. In addition, the statistical Hypotheses Analysis test used in this study validates MATLAB radar_range_eqn program a 95% to 99% near approximation and near accurate calculation of predicted radar range considering the Philippine topographical environment detection criteria calculated during conditions of: clear day; attenuation due to ground and sea clutters; water precipitation like rain, fog, smog and haze; and, the radar pulse integration, which is related to the enhancement of the radar detection performance considering the inherent range and target ambiguity characteristics. The implication of this statistical procedure provides significant impact to the argument that the computer-aided MATLAB radar_range_eqn method is a conclusive and acceptable process for radar performance analysis. This undertaking will be of help to the AFP military decision makers to eventually decide on what appropriate commercial-off-the-shelf (COTS) ADSR equipment that is best and suitable to acquire for the country. Finally, this pioneering effort will enable local engineers as well as students who find passion and interest with radar to further enhance their understanding of radar theory, better appreciate the uncomplicated process that computer-aided analysis offers especially using MATLAB software as a tool and to provide a source reference for their unique and peculiar radar system design requirements.